Köprundans oumbärligheter: Om minimalistisk bärologi - Holmberg, Ulrika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The article explores the practice of carrying simply. Three forms of minimalistic carryology are discussed: 1) carrying just a few things without using any bag or basket, 2) minimalistic carryology as starting point – making room for carrying more later on, and 3) the Matryoshkabag – putting several bags in one to deal with several purchases.